Transient electrical discharges in small devices - Soto, Leopoldo (2001)
Fundamental and applied research on plasmas with high energy density that are unstable and radiate can be done at a relatively low cost with small plasma pinches. In this paper we discuss three experiments using small pinch devices: a capillary discharge, a Z-pinch driven by a small generator, and a low energy plasma focus. The experiments were complemented by magnetohydrodynamics numerical calculations in order to assist the design and physical interpretation of the experimental data. The diagnostics used in the experiments include current and voltage monitors, multipinhole camera, holographic interferometry, and vacuum ultraviolet spectroscopy.